Effects of Daily or Cyclic Teriparatide on Bone Formation in the Iliac Crest in Women on No Prior Therapy and in Women on Alendronate. (21st March 2016) - Dempster, David W; Cosman, Felicia; Zhou, Hua; Nieves, Jeri W; Bostrom, Mathias; Lindsay, Robert
ABSTRACT: There is little information on the effects of combination therapy for osteoporosis at the tissue level. Using quadruple tetracycline‐labeled bone biopsies, we have compared the bone formation response to teriparatide (TPTD) in treatment‐naïve subjects (Rx‐Naïve) and in subjects on prior and ongoing alendronate (ALN) treatment (ALN‐Rx). Three bone envelopes were analyzed: cancellous, endocortical, and intracortical. TPTD was given as a standard, continuous daily injection or as a cyclic regimen (3 months on daily TPTD, 3 months off, 3 months on daily TPTD). Subjects were biopsied at 7 weeks and at 7 months to allow comparison of the bone formation response to the first and second cycles of TPTD. Baseline values for dynamic bone formation indices were lower in ALN‐Rx than Rx‐Naïve subjects. Both Rx‐Naïve and ALN‐RX subjects responded to TPTD with significant increases in bone formation indices at both time points. With cyclic TPTD treatment, the first and second cycles of TPTD stimulated bone formation rate in the cancellous and endocortical envelopes to a similar extent in ALN‐Rx and Rx‐Naïve subjects. However, in Rx‐Naïve patients, bone formation rate (BFR/BS) was higher in patients receiving daily treatment compared with those receiving cyclic TPTD treatment in all three envelopes in the 7‐month biopsies. This suggests that the cyclic approach does not provide a skeletal benefit in treatment‐naive patients. In the 7‐month biopsies, cortical porosity was higher in the Rx‐Naïve group receiving daily TPTD than in all other groups. These data provide supporting evidence at the tissue level for previous biochemical and densitometric data suggesting that addition of either cyclic or daily TPTD to ongoing ALN treatment may be an effective approach for patients with severe osteoporosis already treated with ALN who remain at high risk of fracture. © 2016 American Society for Bone and Mineral Research.